Randomized Comparative Assessment of Three Surgical Cricothyrotomy Devices on Airway Mannequins. (4th May 2019) - Dorsam, Jillian M.; Cornelius, Steven R.; McLean, Julie B.; Zarow, Gregory J.; Walchak, Alexandra C.; Conley, Sean P.; Roszko, Paul J. D.
Abstract: Background : Airway obstruction is the second leading cause of preventable battlefield death, at least in part because surgical cricothyrotomy (SC) failure rates remain unacceptably high. Ideally, SC should be a rapid, simple, easily-learned, and reliably-performed procedure. Currently, 3 SC devices meet Tactical Combat Casualty Care (TCCC) standards: The Tactical CricKit® (TCK), Control-Cric TM (CC), and Bougie-assisted Technique (BAT). However, no previous studies have compared these devices in application time, application success, user ratings, and user preference.Methods : United States Navy Corpsmen (N = 25) were provided 15 minutes of standardized instruction, followed by hands-on practice with each device on airway mannequins. Participants then performed SC with each of the 3 devices in a randomly assigned sequence. In this within-subjects design, application time, application success, participant ratings, and participant preference data were analyzed using repeated-measures ANOVA, regression, and non-parametric statistics at p < 0.05.Results : Application time for CC (M = 184 sec, 95% CI 144-225 sec) was significantly slower than for BAT (M = 135 sec, 95% CI 113-158 sec, p < 0.03) and TCK (M = 117 sec, 95% CI 93-142 sec, p < 0.005). Success was significantly greater for BAT (76%) than for TCK (40%, p < 0.02) and trended greater than CC (48%, p = 0.07). CC was rated significantly lower than TCK and BAT in ease of application, effectiveness, and reliability (each p < 0.01). User preference was significantly (p < 0.01) higher for TCK (58%) and BAT (42%) than for CC (0%). Improved CC blade design was the most common user suggestion.Conclusion : While this study was limited by the use of mannequins in a laboratory environment, present results indicate that none of these devices was ideal for performing SC. Based on slow application times, low success rates, and user feedback, the Control-Cric TM cannot be recommended until improvements are made to the blade design.